The law of blood : thinking and acting as a Nazi - Chapoutot, Johann (The Belknap Press of Harvard University Press, 2018)
The scale and depth of Nazi brutality seem to defy understanding. What could drive people to fight, kill, and destroy with such ruthless ambition? Johann Chapoutot says we need to understand better how the Nazis explained it themselves, and in particular how steeped they were in the idea that history gave them no choice: it was either kill or die.--